Yayasan UMPSA signs collaboration with Public Islamic Bank Berhad for student welfare and entrepreneurship - Wallid Wahidi, Hamzah (UMPSA, 2025)
PEKAN, 4 October 2025 - Yayasan UMPSA signed a collaboration with Public Islamic Bank Berhad (PIBB) in developing areas related to welfare, development, and entrepreneurship among UMPSA students.